Ips typographus and other bark and wood-boring beetles in girdled spruces - Svensson, Petra (2008)
To decrease the number of spruce trees and to create dead wood in some areas several county administration boards have girdled spruces. Girdled spruces have been little studied in terms of the insect fauna. In this study the occurrence of the spruce bark beetle (Ips typographus) and other beetles are investigated in girdled spruce trees (Picea abies) in two provinces in Sweden, Uppland and Jämtland. Girdled trees have been compared with cut trees. The study contains 213 girdled and cut trees. To find out to which extent woodpeckers use girdled spruces as food resource estimation was also done with consideration of how much bark that was picked off each tree.